Strategi Komunikasi Pensponsoran MS Glow For Men Pada Gresini Team MotoGP Dalam Meningkatkan Ekuitas Merek - Berliana Wijayanti Bakti; Dadang Sugiana; Ilham Gemiharto (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
MS Glow for Men is sponsoring the Gresini Racing Team in the 2022 MotoGP season. The suitability between MS Glow for Men and Gresini is considered low. Meanwhile, several previous studies have revealed that the suitability between a sponsor and the sponsored party determines the effectiveness. Gresini's best performance occurred 20 years ago, accompanied by lower popularity on Instagram compared to 11 other teams. These two conditions contradict the goal of sponsorship as a marketing communication tool that requires high visibility. The attractiveness of this sponsorship is also due to its timing in the middle of the season. Based on these factors, this research aims to obtain a comprehensive overview of the reasons and strategies behind this sponsorship. Using a qualitative approach and a case study method, data was gathered through interviews, observations, and documentation studies. The research successfully found that the reasons for sponsorship include the impact of top-level effects, consumer research, external discussions, exposure, connections, values, cooperation, and riders. Sponsorship is conducted to enhance brand awareness, maintain brand image, and expand geographical reach. Focusing on men aged 20-35 who are automotive and MotoGP enthusiasts, MS Glow for Men also extends its sponsorship into six derivative programs, not merely relying on logo placement on the Gresini livery.